UNIVERSITY AS BUSINESS - Vladimir A. Galanov (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article shows the reasons for transforming university into a specific form of business as a result of altering the process of education into the process of organized and mass self-studying based on its computerization. This opportunity is realized by developing such an educational university service, which becomes an article of purchase and sale being therefore the ground for shaping aggregate income of university, on the one hand and realization of student's 'educational capital', on the other. The necessity to transform university into business implies the need to alter educational sphere in such a way so that it could become an important industry whose working mechanisms would allow lecturers and students to join the stratum of well-off and successful members of society. The unique mechanism in this sphere is not the availability of capital (means of production, securities), but the university image and appropriate for this aim differentiation in lecturers' and graduates' remuneration, which can exceed the differences between simple and complicated work.